(untitled) (American Journal of Islam and Society, 2002)
According to Uri Savir, one of the two Israeli chief negotiators who led their country’s team to the Israeli-Syrian talks in Washington, DC, in the 1990s, "there was a sense among both delegations that, if necessary, we could go on living without peace." This sense of a fallback position, engendered mainly by the absence of any urgent existential need to reach a final settlement, is what distinguishes these talks from the IsraeliPalestinian negotiations whose failure is fraught with many risks and unforeseen consequences. Cobban’s book draws on research she conducted for her 1991 book, The Super-Powers and the Syrian-Israeli Conflict, and her 1997 monograph, Syria and the Peace: A Good Chance Missed Published and partly funded by the United States Institute of Peace, a federal institution created by Congress in 1984 to promote research on the peaceful management and resolution of international conflicts, the volume consists of eight chapters, supplemented with a forward by the president of the Institute, Richard Solomon, and a thirty-page section devoted to notes. The book contains no illustrations, photographs, appendices, or bibliographic information; however, it does offer a small map of Syria and Israel at the beginning of the book and an eight-page index section at the end. Although somewhat overshadowed by the off-again-on-again IsraeliPalestinian talks during the 1990s, the Israeli-Syrian negotiations (pro pelled initially by the 1991 Madrid Peace conference) lasted a period of 52 months and, to varying degrees of enthusiasm and success, engaged three successive Israeli governments. The author offers a fascinating account of ...